Applications of some biopolymeric materials as medical implants: An overview. (2022) - Bansal, Priya; Katiyar, Deepti; Prakash, Surya; Rao, N.G. Raghavendra; Saxena, Vidhu; Kumar, Vinay; Kumar, Abhishek
Abstract: Biodegradable materials derived from natural sources are able to substitute synthetic polymer from the biomedical field as well as from other applications due to their advantages in degradability, renewability, lower density, biocompatibility, stability, radiolucent property, etc. As the demand for biomaterial increases, various research has been done to prove their acceptability for implementation in tissue engineering, wound-healing, bone regeneration, and drug delivery rows and medical implants, etc. Implants are the medical devices that are similar in structure of body and able to replace or repair the damaged organ for maintaining the normal body functions. Materials (metals, ceramics, and polymers) used for preparing medical implants have certain disadvantages like immunological rejection by the body, high cost, etc. The focus of the review is to mainly highlight the important properties of biopolymer and their application in medical implants. Although there are various biopolymers that are being utilized in health care system for various reason, but here, the authors mainly discuss few polymers (collagen, gelatin and PLA (Poly Lactic acid) in detail with their approach in various medical devices used in different medical fields like orthopaedics, ophthalmology, cardiology, otolaryngology, dermatology, etc.